Mechanisms of Neuronal Migration during Corticogenesis - Chiaki Ohtaka-Maruyama (Frontiers Research Topics, 2016)
The cerebral cortex plays central roles in many higher-order functions such as cognition, language, consciousness, and the control of voluntary behavior. These processes are performed by the densely interconnected networks of excitatory pyramidal neurons and inhibitory interneurons, and the balanced development of these two types of neuron is quite important. During cortical development, pyramidal neurons and interneurons show quite different migratory behaviors: radial migration and tangential migration, respectively. Pyramidal neurons are generated in the ventricular zone of the dorsal telencephalon, and migrate radially along radial glial fibers toward the pial surface, forming a six-layered cortical structure in an " inside-out" manner. On the other hand, cortical interneurons are generated in the medial and caudal ganglionic eminence in the ventral telencephalon, and follow long tangential migratory paths into the cortex. Defects in these migration processes result in abnormalities in the cortical layer structure and neuronal networks, which may cause various neurological and psychiatric conditions such as epilepsy and schizophrenia. Accordingly, besides basic scientific interest, elucidation of the mechanism of neuronal migration is essential for understanding the pathogenesis of these diseases. This Research Topic includes a series of articles ranging from the basic mechanism of neocortical development to the malformation and evolution of the neocortex. We do hope that the present ebook will further stimulate the interest in the fascinating investigations of neuronal migration and corticogenesis.